Decibel scale sensitivity in analyses of environmental acoustic risks - Batko, Wojciech; Radziszewski, Leszek; Bąkowski, Andrzej (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
The article presents research on the applicability of the psychoacoustic Weber-Fechner law and its constancy across the entire decibel scale. The authors sought to resolve the stated problem based on an assessment of the sensitivity of the decibel scale. Different results were obtained depending on the rule adopted for estimating this characteristic. In the first case, operations of Euclidean algebra were used. In the second case, operations of decibel algebra derived from the psychoacoustic Weber-Fechner law were applied. It was shown that there is no connection between the decibel scale and the conditions of its perception by humans when modelling the examined relationship using Euclidean algebra operations. An acceptable interpretation of the sensitivity of the decibel scale was obtained when it was estimated using the relations of decibel algebra, whose computational relations are consistent with the conditions of human perception of acoustic disturbances. The obtained research results emphasize the key role of decibel algebra in computational procedures used to identify environmental acoustic hazards. They draw attention to the need for broader verification of existing procedures for controlling environmental acoustic hazards, in which there is currently a dualism in modelling identified acoustic threats.